(untitled) (Palíndromo, 2019)
This article investigates my own recent artistic production, establishing relationships between the visual arts and literature and their creative strategies, whereas the work involved here has the book “If a Traveler on a Night of winter”, by Italo Calvino, as a starting point. Relating author’s own ideas and my observations on the novel, in addition to Maurice Blanchot’s writings on literature, I try to deepen my understanding of my recent poetic production and the role the text has acquired in this visual production.